2022
DOI: 10.1136/bmjopen-2022-061453
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised controlled trial of an e-health stepped care approach for the treatment of internet use disorders versus a placebo condition: the SCAPIT study

Abstract: IntroductionExcessive internet use can lead to problems for some individuals. The WHO has introduced Gaming Disorder in the International Classification of Diseases-11 (ICD-11). Previous research has shown that other internet applications can cause serious mental health problems as well. It is important to provide measures of prevention, early intervention and therapy for internet use disorders (IUDs).Methods and analysisThe study ‘Stepped Care Approach for Problematic Internet use Treatment’ is a randomised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The pilot phase sample comprised the first 20 participants included within the online short-term therapy. The online stepped care approach, provided via the smart@net app, contains a screening, and a subsequent assignment to a prevention or an intervention module [14]. To be eligible for participation in the in the SCAPIT study, prospective study participants were required to provide digital informed consent within the smart@net app, be aged between 16 and 67 years, and have a smartphone.…”
Section: Inclusion/exclusion Of Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pilot phase sample comprised the first 20 participants included within the online short-term therapy. The online stepped care approach, provided via the smart@net app, contains a screening, and a subsequent assignment to a prevention or an intervention module [14]. To be eligible for participation in the in the SCAPIT study, prospective study participants were required to provide digital informed consent within the smart@net app, be aged between 16 and 67 years, and have a smartphone.…”
Section: Inclusion/exclusion Of Participantsmentioning
confidence: 99%
“…The intervention module included stepped interventions according to the severity of pathological internet use. Further information on the SCAPIT study procedure can be found in the study protocol [14].…”
Section: Inclusion/exclusion Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals may be 'stepped up' or 'stepped down' in the case of disorder enhancement or reduction. The stepped-care intervention has been implemented in many health domains, including depression and anxiety [34], Internet use disorders [36], and problematic substance use [37]. So far there is no established model of stepped care for AD.…”
Section: Coping Strategies and Correlationsmentioning
confidence: 99%